Reading and Viewing Sex in Early Modern French Vernacular Medicine - Parker, Sarah E. (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2015)
Discussions of sex in early modern medical discourse did not simply legitimize a titillating topic. Medicine was engaged in a broader struggle to establish itself as a legitimate and professionally defined discipline; yet many practitioners marketed their ideas to a non-professional public readership. Using both textual and visual material, this article analyzes the tension between these aims in two sixteenth-century French vernacular works that discussed medical topics related to sex: La Dissection des parties du corps humain (1546) by Charles Estienne and the Erreurs Populaires (first edition, 1578) by Laurent Joubert. These medical authors employed visual and textual strategies to legitimize sexual content and to increase their professional reputations—while nevertheless exploiting the erotic nature of the content in order to improve the marketability of their publications.